Tympanic membrane temperature decreases during head up tilt: relation to frontal lobe oxygenation and middle cerebral artery mean blood flow velocity. (17th November 2017) - Lorr, David; Lund, Anton; Fredrikson, Mats; Secher, Niels H.
Abstract: Introduction: Changes in blood flow influence temperature of surrounding tissues. Since the internal carotid artery (ICA) and internal jugular vein (IJV) neighbor the tympanic membrane, changes in their blood flow most likely determine changes in tympanic membrane temperature (TMT). We sought to evaluate the relationship between changes during a head-up tilt (HUT) induced reduction in cerebral blood flow (CBF) and TMT. Methods: Ten male subjects (age 19–28 years) underwent 50° HUT until presyncope. A non-contact infrared sensor in the ear canal targeted the tympanic membrane. Changes in CBF were monitored by transcranial Doppler which determined the mean blood flow velocity in the middle cerebral artery (MCA Vmean ) and by near infrared spectroscopy assessed frontal lobe oxygenation (Sc O2 ), while skin blood flow (SkBF) was evaluated by laser Doppler flowmetry. Results: During HUT, TMT decreased by 0.6 °C (median; range 0.2 to 1.6 °C) related to a decrease in MCA Vmean (51.0 ± 6.7 to 34.3 ± 5.8 cm/sec (mean ± SD); r = 0.518, p = .002) and Sc O2 (78.6 ± 5.4% to 69.0 ± 5.7%; r = 0.352, p = .043), but not to SkBF (120 ± 78 to 69 ± 37 PU; r = 0.245, p = .142). Conclusion: During an orthostatic challenge TMT decreases and the decrease is related to a reduction in CBF as indicated by MCA Vmean and Sc O2, but not to SkBF. We consider TMT holds potential for non-invasive assessment of changes in cerebral perfusion.